2021
DOI: 10.1111/1759-7714.14282
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of lung cancer and benign lung lesion using salivary metabolites: A preliminary study

Abstract: Background Saliva is often used as a biomarker for the diagnosis of some oral and systematic diseases, owing to the non‐invasive attribute of the fluid. In this study, we aimed to identify salivary biomarkers for distinguishing lung cancer (LC) from benign lung lesion (BLL). Materials and Methods Unstimulated saliva samples were collected from 41 patients with LC and 21 with BLL. Salivary metabolites were comprehensively analyzed using capillary electrophoresis mass spectrometry. To differentiate between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…As the degree of damage to the lymph node lesion rises, the level of imidazole compounds also increases. Thus, the level of imidazole compounds in saliva can be used as an important biomarker for lung cancer detection. , …”
Section: Resultsmentioning
confidence: 99%
“…As the degree of damage to the lymph node lesion rises, the level of imidazole compounds also increases. Thus, the level of imidazole compounds in saliva can be used as an important biomarker for lung cancer detection. , …”
Section: Resultsmentioning
confidence: 99%
“…Besides oral diseases, e.g., [ 130 ], salivary analysis also has a high level of potential applications for the diagnostics of various systemic diseases such as Sjörgen’s syndrome [ 65 , 66 ], as well as distant malignancies, such as breast cancer [ 131 ] and its recurrence [ 132 ], lung cancer [ 133 , 134 ] and prostate cancer [ 135 ] (recent developments in the diagnosis and prognostic monitoring of cancers are fully outlined and reviewed in Ref. [ 2 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary study by Takamori et al [ 52 ] identified salivary metabolites for distinguishing lung cancer (LC) from benign lung lesions (BLL). Among ten different salivary metabolites, only tryptophan concentrations were significantly decreased in LC patients compared with BLL patients.…”
Section: Discussionmentioning
confidence: 99%
“… Quality assessment, including the main potential risk of bias (risk level: green—low, yellow—unspecified, red—high; quality score: green—good, yellow—intermediate, red—poor) [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. …”
Section: Methodsmentioning
confidence: 99%